2021
DOI: 10.1177/10436596211057895
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Adult Men Who Are Homeless Accessing Care: A Qualitative Study

Abstract: Introduction: Homeless individuals experience increased rates of chronic physical and mental health conditions. They also experience difficulty accessing care and poor health outcomes compounded by social and economic factors, such as housing insecurity, unemployment, and limited social support. The purpose of this study was to describe the perceptions of homeless individuals related to their health and experiences accessing care. Method: Qualitative descriptive methods and content analysis were used to gather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 36 publications
(45 reference statements)
0
15
0
Order By: Relevance
“…Twelve studies did not define a specific health service context and instead reported information on general patient experiences engaging with any area of health services. The tools utilised across the studies included interviews (n = 20), focus groups [29,31,[33][34][35][36] (n = 7), surveys [32,[37][38][39][40][41][42][43] (n = 8), and qualitative ranking exercise [44] (n = 1) to facilitate exploration of patient experience. The qualitative ranking exercise asked PEH and experts to prioritise 16 aspects of PHC.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twelve studies did not define a specific health service context and instead reported information on general patient experiences engaging with any area of health services. The tools utilised across the studies included interviews (n = 20), focus groups [29,31,[33][34][35][36] (n = 7), surveys [32,[37][38][39][40][41][42][43] (n = 8), and qualitative ranking exercise [44] (n = 1) to facilitate exploration of patient experience. The qualitative ranking exercise asked PEH and experts to prioritise 16 aspects of PHC.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…to care, the availability and flexibility of services, and geographic and financial accessibility. The most common patient experiences reported within this domain were timeliness of treatment [31,[33][34][35][36]59], flexibility and convenience of services [45,46,51,56] (especially those offering co-located [46,[53][54][55] or drop-in services [34,45,53,56,59]), the physical and organisational environment [46], and the location of services [33,34,[53][54][55].…”
Section: Domainsmentioning
confidence: 99%
See 2 more Smart Citations
“…I read with interest the article by Henderson et al in the March 2022 issue of the Journal of Transcultural Nursing (Henderson et al, 2022). I commend the authors for their careful study of the perceptions of homeless individuals regarding their health and their experiences in seeking health care.…”
mentioning
confidence: 99%